Perception of intern doctors about the newly introduced assessment system in the final professional MBBS examination (Bangladesh Journal of Medical Education, 2014)
It was a descriptive study. The objective was to find out the perception of intern doctors regarding newly introduced assessment system in final professional MBBS examination which was held in July 2011. Data were collected from 500 inter doctors of selected medical colleges by using self administered questionnaire. It was found that majority (84%) of the respondent expressed their satisfaction with the newly introduced assessment method .Of the students 95.5% mentioned that SAQ is better than Essay questions. Inclusion of MCQ, SOE and OSCE in examination is worthy was opined by about 86.6%, 81.7%, 78% of the students respectively. Nearly eighty nine (89%) percent respondents thought that adding of a certain percentage of mark of formative assessment in final examination is better. About 29% of respondents said that examination phobia in oral /viva is not reduced by introducing SOE, 26.2% believed that all examinees are not judged in same standard by examiners by means of OSCE and 31% respondents believed that result of examination in SOE, some extent depends upon the examiners desire and intention. So, it reveals that the new assessment method is not implemented properly. Students also identified strengths and weakness of the new assessment. DOI: http://dx.doi.org/10.3329/bjme.v3i1.18592 Bangladesh Journal of Medical Education Vol.3(1) 2012: 22-25